Aging Adventure Athletes Assess Achievements and Alter Aspirations to Maintain Self-Esteem - Buckley, Ralf C. (Frontiers in Psychology, 2018)
Achievements and capabilities influence the self-esteem of skilled adventure athletes. Self-esteem affects individual mental health. Ageing commonly reduces adventure capabilities. To avoid loss in self-esteem, ageing adventure athletes are forced to adjust their aspirations. Here I examine this process using participant observation, ethnographic and autoethnographic approaches. The qualitative data for this analysis are derived from 60 years’ experience in outdoor adventure activities, and ~30,000 person-hours of participant observation. I argue that individuals assess their own capabilities against a set of specific feats. For some activities, successful completion of a specific feat is known as nailing it. The selection of these feats depends on factors such as activity and geographic location, as well as individual experience and peer comparisons. I examine the detailed process using a single feat repeated over a period of decades, the bubble-line kayak run through Lava Falls on the Grand Canyon of the Colorado River. I compare other examples of nail or fail to construct a general framework for self-esteem in ageing adventure athletes, with both physical and psychological feedback loops. I also identify two key thresholds, as ageing adventure athletes recognise their declining skills. These may apply to ageing more broadly, beyond outdoor adventure.